The effect of plant-based dietary supplements on weight reduction and the regulation of metabolism - Mizera, Krzysztof Maciej; Mizera, Justyna (Journal of Education, Health and Sport, 2022)
Introduction: As overweight and obesity have become a disease of civilization, more and more people try to accelerate weight reduction in various ways. One of the methods used is the use of dietary supplements. Methods: 30 overweight or obese people took part in the study. At the beginning and at the end of the study, each participant was measured and weighed on a professional Tanita DC-360 body composition analyzer. The age in both groups was similar - the average was about 37 years old, height and weight in the group of men was greater. The subjects used the dietary supplement for 6 weeks. At that time, they did not take any other dietary supplements, followed the diet as before, did not consume caffeine and did not undertake any physical activity at that time. Results: There were significant differences in the results between men and women for the field of physical. Women had a significantly higher result, which means that they were more susceptible to the effects of supplements. Individuals who achieved a weight loss score significantly higher for the field of physical. It also turned out that although weight loss and the absence of gastrointestinal problems during supplementation were observed in both groups, they occurred in a greater amount in women than in men, and the differences these were statistically significant. Higher effectiveness among women may be the result of differences in the functioning of the endocrine system, although it is certainly worth taking a closer look at this issue. 40% of respondents did not notice any weight loss while taking supplementation. Conclusions: Plant-based supplements reduce body weight and metabolism, and may also alleviate gastrointestinal discomfort. In addition, they improve digestion in general, increase vitality and, to a small extent, may contribute to the improvement of the immune system.